2019
DOI: 10.1002/admi.201801920
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Aggregation and Dispersion of Particles at a Liquid–Liquid Interface Using Space Charge Injection

Abstract: large interparticle spacing, akin to Wigner crystals, under the combined effect of the attractive and repulsive interparticle interactions. These forces are long-ranged compared to corresponding interactions in bulk media. The attractive interaction between interfacial particles are believed to originate from interface undulation around individual particles due to nanoscale surface roughness and heterogeneity, [14,15] whereas the long-ranged repulsion arises from the asymmetric surface charge distribution acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The CB-Au NP nanocomposites can also be embedded into the shell of microcapsules which allows the detection of analytes that are selectively encapsulated within the cavity of microcapsules 43,44 . The formation of such kind of CB-mediated microcapsules benefits from the synergetic effect of formation of supramolecular CB8 ternary complex [45][46][47] and high detachment energy of NPs from the liquid-liquid interface [48][49][50][51] . Zhang et al 43 first reported the fabrication of CB8-Au NPs supramolecular microcapsule via a single-step approach using a droplet microfluidics technique.…”
Section: Lab-on-a-chip Applications Through Implementing Cb-au Np Nan...mentioning
confidence: 99%
“…The CB-Au NP nanocomposites can also be embedded into the shell of microcapsules which allows the detection of analytes that are selectively encapsulated within the cavity of microcapsules 43,44 . The formation of such kind of CB-mediated microcapsules benefits from the synergetic effect of formation of supramolecular CB8 ternary complex [45][46][47] and high detachment energy of NPs from the liquid-liquid interface [48][49][50][51] . Zhang et al 43 first reported the fabrication of CB8-Au NPs supramolecular microcapsule via a single-step approach using a droplet microfluidics technique.…”
Section: Lab-on-a-chip Applications Through Implementing Cb-au Np Nan...mentioning
confidence: 99%